Knowledge, Attitude, and Practice of Mothers with Children under five in the Villages Regarding Self-Medication in Ardakan city, Iran - Zahra Zarei Mahmoudabadi; Ameneh Marzban; Abdolrazagh Marzban; Farokhlegha Servat (Hamadan University of Medical Sciences, 2022)
Background and Objective: Nowadays, medication abuse and, in general, self-medication are among the biggest socio-economic and economic problems in different societies such as Iran. This study aimed to investigate the knowledge, attitude, and practice of mothers with children under five years old about self-treatment in Ardakan villages, Iran. Materials and Methods: This descriptive cross-sectional study was carried out on 350 mothers with children under 5 years of age in Ardakan, 2020. The tool used to gather the required data was a four-part questionnaire (demographic, knowledge, attitude, and practice). Data were analyzed using descriptive and analytical statistics. Results: The mean scores of knowledge, attitude, and practice were obtained at 5.17±4.11, 25.08±8.74, and 3.52±4.31, respectively. It was found that 58% of the mothers had poor knowledge, 51% had a poor attitude, and 62% had low self-medication practice, respectively. There was a statistically significant relationship between the mean knowledge score and mothers' education level. There was also a statistically significant relationship between the variables of mean practice score and family income adequacy. The most important sources of information for mothers with children under the age of five about self-medication were the Internet and social networks, followed by family and friends (P<0.05). Conclusion: The results of the study showed that self-medication was very high in the study population and knowledge about the complications of self-medication in children was low, which should be considered an alarm by the authorities. The implementation of educational programs and workshops and distribution of education aids when mothers visit health centers can be effective in raising mothers' knowledge, improving their attitude, and forming the correct behavior.